Hubungan Pola Asuh dan Trauma dengan Kejadian Bullying di SMP Nurul Khoir Kota Jambi - Putri, Vevi Suryenti; Putri, Miko Eka; Hidayat, Muhammad; Nurfitriani, Nurfitriani (Jurnal Akademika Baiturrahim Jambi, 2025)
Adolescence is a transitional phase that is vulnerable to various social problems, one of which is bullying. Bullying has a serious impact on adolescents’ psychological development, including trauma, decreased academic achievement, and the risk of long-term psychosocial disorders. This study aimed to determine the relationship between parenting style and trauma with bullying incidents among students of Nurul Khoir Junior High School in Jambi City. This research used a quantitative method with a cross-sectional design. The population was all students of Nurul Khoir Junior High School with a total sample of 60 respondents obtained through total sampling. The research instrument was a questionnaire consisting of respondents’ identities, parenting style, trauma experience, and bullying incidents. Data were analyzed using the chi-square test with a 95% confidence level. The results showed that more than half of the respondents had experienced bullying (60.0%), most reported authoritarian parenting (41.7%), and more than half experienced trauma (56.7%). Bivariate analysis indicated a significant relationship between parenting style and bullying incidents (p = 0.032) as well as trauma and bullying incidents (p = 0.018). The study concludes that authoritarian parenting and trauma experiences increase the risk of bullying among adolescents. It is recommended that schools strengthen anti-bullying policies, provide counseling services, and involve teachers and parents in prevention programs. Parents are encouraged to apply an authoritative parenting style characterized by open communication, emotional support, and balanced supervision to minimize the risk of bullying